Socioecological Dynamic of a Rural Community at San Luis, Barrancabermeja - Quintero-Cardozo, Jesús; Patiño-Núñez, Adriana; Riva, Henrique; Torres-Angulo, Kelly Cristina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article analyzes the socio-ecological dynamics of local communities settled in the village of San Luis in the municipality of Barrancabermeja, Santander, Colombia. We analyze patterns of behavior of communities, the natural environment and the impact of institutions that are a part of the system. Using the conceptual and methodological tools of the institutional analysis and development framework (IAD), it is intended to locate the set of formal and informal rules that influence the man / nature relationship and unveil institutional arrangements to identify conflicts with animal species (specially felines) and conservation strategies. The conclusion is that most institutional failures are given by the conflicts between the different groups that are part of the territory (old communities, new communities of people displaced by violence and academia). This divergence is fueled by social inequality and disparity of support from the government that also encourage displaced communities to use much more resources focused on high productivity, on the other hand, old communities have a resource use focused on subsistence or low-scale trade. It is necessary to strengthen rural institutions and put formal rules in action to achieve synergies that increase the efficiency in the use of natural resources to improve the relationship between man and nature.